Benzoxazepines Achieve Potent Suppression of IL‐17 Release in Human T‐Helper 17 (TH17) Cells through an Induced‐Fit Binding Mode to the Nuclear Receptor RORγ. Issue 2 (10th November 2015) - Olsson, Roine I.; Xue, Yafeng; von Berg, Stefan; Aagaard, Anna; McPheat, Jane; Hansson, Eva L.; Bernström, Jenny; Hansson, Pia; Jirholt, Johan; Grindebacke, Hanna; Leffler, Agnes; Chen, Rongfeng; et al.
Abstract: RORγt, an isoform of the retinoic acid‐related orphan receptor gamma (RORc, RORγ), has been identified as the master regulator of T‐helper 17 (TH 17) cell function and development, making it an attractive target for the treatment of autoimmune diseases. Validation for this target comes from antibodies targeting interleukin‐17 (IL‐17), the signature cytokine produced by TH 17 cells, which have shown impressive results in clinical trials. Through focused screening of our compound collection, we identified a series of N‐ sulfonylated benzoxazepines, which displayed micromolar affinity for the RORγ ligand‐binding domain (LBD) in a radioligand binding assay. Optimization of these initial hits resulted in potent binders, which dose‐dependently decreased the ability of the RORγ‐LBD to interact with a peptide derived from steroid receptor coactivator 1, and inhibited the release of IL‐17 secretion from isolated and cultured human TH 17 cells with nanomolar potency. A cocrystal structure of inverse agonist15 (2‐chloro‐6‐fluoro‐ N ‐(4‐{[3‐(trifluoromethyl)phenyl]sulfonyl}‐2, 3, 4, 5‐tetrahydro‐1, 4‐benzoxazepin‐7‐yl)benzamide) bound to the RORγ‐LBD illustrated that both hydrophobic interactions, leading to an induced fit around the substituted benzamide moiety of15, as well as a hydrogen bond from the amide NH to His479 seemed to be important for the mechanism of action. This structure is compared with the structure of agonist25 ( N ‐(2‐fluorophenyl)‐4‐[(4‐fluorophenyl)sulfonyl]‐2, 3, 4, 5‐tetrahydro‐1, 4‐benzoxazepin‐6‐amine ) and structures of other known RORγ modulators. Abstract : ROR out ! Novel benzoxazepine‐based ligands for RORγ, the nuclear receptor responsible for development and differentiation of human T‐helper 17 (TH 17) cells, inhibit interleukin‐17 (IL‐17) secretion with nanomolar potency. A cocrystal structure of an inverse agonist bound to the RORγ ligand‐binding domain revealed that both an induced fit, as well as a hydrogen bond to His479 are necessary to disrupt the agonist conformation of the receptor.